The effect of Sumac on cardiometabolic parameters in adults: a systematic review and meta-analysis of randomized controlled trials - Jafarpour, Amirhosein; Jalali, Saeedeh; Akhlaghi, Masoumeh; Amlashi, Manoochehr Amin (Frontiers in Nutrition, 2024)
The current evidence on the effect of Sumac consumption on cardiovascular parameters has produced controversial findings. Methods: We systematically searched several databases, including PubMed-Medline, SCOPUS, and ISI Web of Science, to find eligible studies until January 2023. Meta-analysis to calculated the weighted mean difference (WMD) and 95 %CI, Sub-group meta-analysis and meta-regression analysis were conducted throughout the study.Results: 16 randomized controlled trials comprising a total number of 1225 participants were included. The results of meta-analysis revealed that Sumac significantly affected low-density lipoprotein (WMD: -8.66 mg/dl; 95% CI: -14.2, -3.12), high-density lipoprotein (WMD: 3.15 mg/dl; 1.99,4.31), triglycerides (WMD: -11.96 mg/dl; -19.44, -4.48), fasting blood glucose (WMD: -4.15 mg/dl; -7.31, -0.98), insulin (WMD: -1.72; -3.18, -0.25), homeostasis model assessment of insulin resistance (HOMA-IR) (WMD: -0.61; -1.22, -0.01), and anthropometric indices (P< 0.05). Moreover, the results significantly reduced total cholesterol when the intervention duration was ≥12 weeks (WMD: -8.58 mg/dl; -16.8, -0.37). Conclusion: These findings suggest that Sumac is potentially an effective complementary intervention to improve cardiometabolic parameters. Thus, patients could utilize Sumac as part of their diet to improve their overall cardiometabolic status.